👤

[tex] \frac{4 y^{3} }{x- y^{2} } [/tex]+[tex] \frac{3xy+ y^{3} }{ y^{2} -x} [/tex]
vă rog urgent HELP
pun și coronița


Răspuns :

numaratorul=4 y³ ( y² -x) + ( x- y² ) y( 3x +y²) = y ( 4y⁴ - 4xy² +3x² - 3xy² +xy² -y⁴)=
= y ( 3y⁴ -6 xy² +3x² )= 3y ( y⁴ -2 xy² +x²)= 3y( y² -x)²
numitorul=                                            - ( y² -x) ( y² -x) 
                                                  ---------------------------------------- impartire
                                                            = - 3 y